Long noncoding RNA expression in the cervix mid-pregnancy is associated with the length of gestation at delivery. Issue 7 (3rd July 2018) - Burris, Heather H.; Just, Allan C.; Haviland, Miriam J.; Neo, Dayna T.; Baccarelli, Andrea A.; Dereix, Alexandra E.; Brennan, Kasey J.; Rodosthenous, Rodosthenis S.; Ralston, Steven J.; Hecht, Jonathan L.; Hacker, Michele R.
ABSTRACT: Infants born preterm are at increased risk of multiple morbidities and mortality. Why some women deliver preterm remains poorly understood. Prior studies have shown that cervical microRNA expression and DNA methylation are associated with the length of gestation. However, no study has examined the role of long noncoding RNAs (lncRNAs) in the cervix during pregnancy. To determine whether expression of lncRNAs is associated with length of gestation at delivery, we analyzed RNA from cervical swabs obtained from 78 women during pregnancy (mean 15.5, SD 5.0, weeks of gestation) who were participating in the Spontaneous Prematurity and Epigenetics of the Cervix (SPEC) Study in Boston, MA, USA. We used a PCR-based platform and found that 9 lncRNAs were expressed in at least 50% of the participants. Of these, a doubling of the expression of TUG1, TINCR, and FALEC was associated with shorter lengths of gestation at delivery [2.8 (95% CI: 0.31, 5.2); 3.3 (0.22, 6.3); and 4.5 (7.3, 1.6) days shorter respectively]. Of the lncRNAs analyzed, none was statistically associated with preterm birth, but expression of FALEC was 2.6-fold higher in women who delivered preterm vs. term ( P = 0.051). These findings demonstrate that lncRNAs can be measured in cervical samples obtained during pregnancy and are associated with subsequent length of gestation at delivery. Further, this study supports future work to replicate these findings in other cohorts and perform mechanistic studies to determine the role of lncRNAs in the cervix during pregnancy.